Changes in the intensity and impact of factors influencing consumer behaviour in the food market over time - Irena Antošová; Jana Stávková (Agricultural Economics (AGRICECON), 2023)
The paper aims to identify the changes and intensity of the factors influencing consumers' purchasing decision-making process in the food market. The research offers a unique comparison of the situation between the years 2007 and 2022 and reveals the emerging factors affecting consumer decisions. The authors conducted a representative questionnaire survey (N = 686) to determine the influence of individual factors. The data were processed using factor analysis, which allowed for the reduction of the number of factors (20) to four determinants covering 61% of the total variability in the dataset. The determinants of consumer purchasing decisions include traditional promotional elements, product parameters, newly formed factors based on sustainability and health awareness trends, and price discounts. Consumer behaviour appears to be influenced by a wide range of short- and long-term factors, and it is necessary to look at it comprehensively over a longer time horizon, taking current trends into account.